2005
DOI: 10.1113/jphysiol.2005.094151
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of chemoreceptor and baroreceptor reflexes by hypoxia and hypercapnia – a mechanism for promoting hypertension in obstructive sleep apnoea

Abstract: Asphyxia, which occurs during obstructive sleep apnoeic events, alters the baroreceptor reflex and this may lead to hypertension. We have recently reported that breathing an asphyxic gas resets the baroreceptor-vascular resistance reflex towards higher pressures. The present study was designed to determine whether this effect was caused by the reduced oxygen tension, which affects mainly peripheral chemoreceptors, or by the increased carbon dioxide, which acts mainly on central chemoreceptors. We studied 11 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
2
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 50 publications
(54 reference statements)
5
110
2
7
Order By: Relevance
“…MAP was increased during hypercapnia, whereas HR was increased during hypoxia and hypercapnia. This has been reported by some investigators (10,29,36) but not by others (21,36). We found that TPR was reduced and CO increased, which would seem at odds with the known potentiating effects of hypoxia and hypercapnia on the sympathetic nervous system (36).…”
Section: Discussioncontrasting
confidence: 55%
“…MAP was increased during hypercapnia, whereas HR was increased during hypoxia and hypercapnia. This has been reported by some investigators (10,29,36) but not by others (21,36). We found that TPR was reduced and CO increased, which would seem at odds with the known potentiating effects of hypoxia and hypercapnia on the sympathetic nervous system (36).…”
Section: Discussioncontrasting
confidence: 55%
“…These changes develop more rapidly in infants, but the body stores which buffer changes in CO 2 are correspondingly much smaller in infancy. At both ages, the pressor response outlasts the stimulus, most likely due to residual adrenergic stimulation by catecholamines released into the blood from the adrenal (21). The similarities between adults and infants suggest that (i) this cardiovascular chemoreflex arc is normally well developed at or soon after birth and (ii) elements of it may be fine-tuned as the heart and nervous systems mature, but the response itself changes little with age.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, Cooper et al (44) reported that the effect of both peripheral and central chemoreceptors on baroreflex function may contribute to promoting hypertension in patients with obstructive sleep apnea.…”
Section: So-called 'Cirrhotic' Appearance (Asterisk) Hematoxylin Andmentioning
confidence: 99%